Involvement of the avian dorsal thalamic nuclei in homing pigeon navigation - Jorge, Paulo E. (2017)
The navigational ability of birds has been a focus of popular and scientific interest for centuries, but relatively little is known about the neuronal networks that support avian navigation. In the brain, regions like the piriform cortex, olfactory bulbs, hippocampal formation, vestibular nuclei, and the wulst, are among the brain regions often discussed as involved in avian navigation. However, despite large literature showing a prominent role of some anterior and dorsal thalamic nuclei in mammalian spatial navigation, little is known about the role of the thalamus in avian navigation. Here, we analyzed a possible role of the dorsal anterior thalamic nuclei in avian navigation by combining olfactory manipulations during the transport of young homing pigeons to a release site and c-Fos immunohistochemistry for the mapping brain activity. The results reveal that odor modulated neurons in the avian dorsolateral lateral (DLL) subdivision of the anterior thalamic nuclei are actively involved in processing outward journey, navigational information. Outward journey information is used by pigeons to correctly determine the homeward direction. DLL participation in acquiring path-based information, and its modulation by olfactory exposure, broadens our understanding of the neural pathways underlying avian navigation.